2020
DOI: 10.1186/s12889-020-09725-y
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Children’s physical activity level and sedentary behaviour in Norwegian early childhood education and care: effects of a staff-led cluster-randomised controlled trial

Abstract: Background A growing body of evidence suggest that the children’s physical activity (PA) level in early childhood education and care (ECEC) settings are insufficient. Since most children attend ECEC settings for many hours on most days of the week, and these institutions reach children across the socioeconomic spectrum, the ECEC settings may serve as an ideal avenue for increasing physical activity level, reduce sedentary time and enhance the overall health of young children. This paper investi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(38 citation statements)
references
References 43 publications
0
37
0
Order By: Relevance
“…Studies underlined that, with increasing age, motoric abilities are improved, and the females reach the top in motoric abilities at age 14-15 [59][60][61]. The researchers showed that more than 80% of the females and 70% of the males at age 11 do not have recommended physical activity, whereas 85% of the females and 69% of the males do not have recommended physical activity at age 13, which indicates that the prevalence of insufficient physical activity is higher among females than males [62][63][64]. A longitudinal study [65] which was realized in three-year period shows that females spend more hours in sitting activities (reading, watching TV, working on a computer) in comparison to the males who usually spend their spare time in playing sports or various types of games.…”
Section: Discussionmentioning
confidence: 99%
“…Studies underlined that, with increasing age, motoric abilities are improved, and the females reach the top in motoric abilities at age 14-15 [59][60][61]. The researchers showed that more than 80% of the females and 70% of the males at age 11 do not have recommended physical activity, whereas 85% of the females and 69% of the males do not have recommended physical activity at age 13, which indicates that the prevalence of insufficient physical activity is higher among females than males [62][63][64]. A longitudinal study [65] which was realized in three-year period shows that females spend more hours in sitting activities (reading, watching TV, working on a computer) in comparison to the males who usually spend their spare time in playing sports or various types of games.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, 2-year-olds in New Zealand (NZ) spend 1.5 h/day in sedentary screen use [ 4 ], consequently reducing active time. Despite many countries, including NZ [ 5 ], having (nutrition and) PA guidelines, low levels of, and low intensity of, PA have been observed in childcare settings, indicating that children may not be fulfilling their PA requirements [ 1 , 2 , 6 ]. As such, evidence suggests that children are not performing sufficient PA to ensure improved bone density, aerobic fitness and motor skills [ 7 , 8 , 9 ]; thus, the assumption that toddlers and young children are naturally active [ 1 , 2 ] may be damaging to children’s wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to children at home, children in childcare are less likely to engage in PA [ 11 , 12 , 13 ]. As most NZ children aged 3- and 4-years-old (86% and 92%, respectively) are enrolled in early learning services [ 14 ], these environments are important for the promotion of practices that contribute to children’s wellbeing [ 6 , 15 ]. United Nations International Children’s Emergency Fund (UNICEF) Innocenti [ 16 ] ranked NZ 35th out of 38 OECD and EU countries for overall child wellbeing (38th for mental well-being, 33rd for physical health, and 22nd for skills), thus further highlighting the critical need for NZ to have a stronger focus on childhood wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…While this allowed for a broad range of strategies to be captured, potential bias (e.g., confounding bias) of the studies included may reduce the internal validity of the overall findings [ 16 ]. Given a number of childcare-based RCTs have been published recently [ 43 , 44 , 45 ], future systematic reviews should capture and draw conclusions using a broader RCT evidence base. Finally, all the included reviews were published in English, and the majority of the included studies within the reviews were undertaken in high-income countries.…”
Section: Discussionmentioning
confidence: 99%